Improving Health Care by Understanding Patient Preferences: The Role of Computer Technology - Brennan, Patricia Flatley (American Medical Informatics Association, 1998)
If nurses, physicians, and health care planners knew more about patients' health-related preferences, care would most likely be cheaper, more effective, and closer to the individuals' desires. In order for patient preferences to be effectively used in the delivery of health care, it is important that patients be able to formulate and express preferences, that these judgments be made known to the clinician at the time of care, and that these statements meaningfully inform care activities. Decision theory and health informatics offer promising strategies for eliciting subjective values and making them accessible in a clinical encounter in a manner that drives health choices. Computer-based elicitation and reporting tools are proving acceptable to patients and clinicians alike. It is time for the informatics community to turn their attention toward building computer-based applications that support clinicians in the complex cognitive process of integrating patient preferences with scientific knowledge, clinical practice guidelines, and the realities of contemporary health care.